Studi Etnomedisin Tumbuhan Berkhasiat Obat Maag dan Asam Urat di Desa Sukaharja, Lebak - Banten - Rindita; Sherley; Tuti Rahmawati; Diah Suci Handayani (Universitas Bengkulu, 2023)
The utilization of medicinal plants as traditional medicine is one of the Indonesian heritages that needs to be preserved. Many methods can apply conservation for medicinal plants, includingethnomedicinal study. This study was conducted in Sukaharja Village, Cikulur, Lebak District, Banten, where its society still uses medicinal plants to cure many kinds of diseases, such as gastritisand gout arthritis. The aims of this study are: to make a list of plants used, which part of plants used, how to use it as a traditional medicine, and to count the use value (UV) of each species used. This study used a descriptively quantitative method, with purposive and snowball sampling. From this study, we found 25 species of plants that have been used to treat those 2 dis eases: 14 species of plants to cure gastritis, 16 species for treating gout arthritis, and 5 species can be used for both. Parts of the plant used as medicinal herb are rhizomes, herbs, and leaves that are boiled, grated, and consumed twice daily . From UV analysis, plants with the highest UV for treating gout arthritis are: Plantago major (UV 0.67), Syzygium polyanthum (UV 0.63), Physalis angulata (UV 0.61), Pandanus amaryllifolius (UV 0.57),and Curcuma zanthorrhiza (UV 0.54). Plants with the highest UV for curing gastritis are Lantana camara (UV 0.66), turmeric (Curcuma longa, UV 0.58), billygoat-weed (Ageratum conyzoides, UV 0.54), temulawak (Curcuma zanthorrhiza, UV 0.52), and Gymnanthemum amygdalinum (UV 0.46).